PENGARUH MOTIVASI, BUDAYA ORGANISASI DAN KEPEMIMPINAN KEPALA SEKOLAH TERHADAP KINERJA GURU SMA NEGERI 1 TORJUN KABUPATEN SAMPANG - jurnalmap map; Siti Sulihah; C. Sri Hartati (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2020)
This research was conducted in SMA Negeri 1 Torjun Sampang Regency with the number of research samples as many as 32 personnel, The purpose of this study is 1) To describe the motivation, organizational culture, leadership of principal and teacher performance, 2) To know the effect simultaneously the motivation, organizational culture, and leadership of the principal against the performance of teachers, 3) To know influence of motivation on teacher performance, 4) To know influence of organizational culture on teacher performance of SMA Negeri 1 Torjun Kabupaten Sampang; 5) To know influence of the principal's leadership on teacher performance. The results showed that simultaneously, motivation, organizational culture and leadership of principals have a significant effect on the performance of teachers. Partially, motivation, organizational culture and leadership of principal have a significant effect on teacher performance.Keywords: motivation, organizational culture, principal leadership, teacher performance